Implementation of Strengthening Character Education in Pancasila Education Learning - Martini, Nella; Putra, Chandra Anugrah; Rahmaniati, Rita (International Journal of Universal Education, 2023)
Background: The values in Strengthening Character Education can improve students' character. Aim: This research aims to determine the implementation of strengthening students' character education in Pancasila education learning. Method: This research uses qualitative methods, with the research subjects being principals, teachers, and students at State Elementary School Muhammadiyah Kuala Kapuas. Observation, interviews, and documentation are used to collect this data. Results and Dıscussion: The research results show that (1) there is a lack of learning planning contained in the Independent Curriculum related to Strengthening Character Education; (2) The implementation of the learning process at State Elementary School Muhammadiyah Kuala Kapuas only uses discussion, question and answer and lecture methods; (3) Strengthening Character Education is the most important thing in the Independent Curriculum and in evaluating the instillation of character values that have been taught in the learning process. Conclusion: In the learning planning contained in the Merdeka Curriculum, the Merdeka Curriculum was developed as a more flexible curriculum framework while focusing on essential material and developing the character and competencies of students. Integration of Strengthening Character Education is contained in the teaching module, which contains five main character values. Apart from that, learning Pancasila education at State Elementary School Muhammadiyah Kuala Kapuas emphasizes the habit of discipline in all things to train students to have strong character and emphasizes a variety of learning methods and emotional closeness with students to support comfort when learning takes place in class.